TEACHER'S EFFORTS TO IMPROVE STUDENTS' LEARNING MOTIVATION OF CLASS X OF STATE VOCATIONAL HIGH SCHOOL 1 AMPEK ANGKEK IN ART AND CULTURE SUBJECT - Premier Zega, Frendy; Minawati , Rosta; Mulyadi (PT. Antis International Publisher, 2024)
Objective: This study investigates strategies to enhance students' motivation in Arts and Culture subjects at SMK Negeri 1 Ampek Angkek. Motivation is essential for academic success, yet observations show low motivation levels among students in this area. Method: A qualitative approach was used to explore factors affecting learning motivation and identify effective teaching strategies. Data were collected through literature studies, unstructured interviews, observations, and documentation. Results: Key findings reveal that low motivation stems from inadequate learning facilities, lack of teacher engagement, family, peer, and environmental influences. Effective strategies to boost motivation include awarding points, providing grades, employing varied teaching methods, assigning tasks, offering praise, implementing appropriate punishments, administering tests, and fostering collaboration with students. These approaches create an engaging learning environment, addressing individual student needs and challenges. Novelty: This study highlights a comprehensive, context-specific approach for addressing motivation challenges in vocational schools, particularly in creative subjects like Arts and Culture. Unlike previous studies, it emphasizes the interconnected role of intrinsic and extrinsic motivators tailored to vocational students' unique needs.